2021
DOI: 10.20944/preprints202104.0540.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

One-bath One-step Dyeing of Polyester/Cotton (PC) Blends Fabric With Disperse Dyes After Acetylation of Cotton

Abstract: Usually, the two-bath dyeing process using disperse dyes and reactive dyes separately was employed for the dyeing of PC blends. The cost of the double bath, dyeing cycle, energy consumption and chemical consumption is quite higher than the one-step or single bath dyeing methods. In this study, the one-bath dyeing process using one kind of dye was investigated. Polyester cotton blends dyed in one-bath one-step dyeing methods with disperse dye after surface modifications of cotton by acetylation methods were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…After rinsing, the coloring was reduced over 15 minutes at 60°C in a water-based solution of 2 gpl sodium hydroxide (NaOH) as well as 2 gpl sodium hydrosulphite (Na 2 S 2 O 4 ). The investigation indicated that a 16% acetylation reagent dosage and a 2.5-hour reaction duration yielded a percent acetylation of 34 as the ideal measurement of acetylation [34]. Scheme 9: Process of cellulose's acetylation reactivity [34] The dyeing experiment's findings additionally indicated that, compared to the untreated halfbleached cloth, weft tensile strength was reduced by 9% and warp strain toughness by roughly 12% at a temperature of 120C.…”
Section: Dyeing Of Polyester/cotton Fabric Blendmentioning
confidence: 99%
See 3 more Smart Citations
“…After rinsing, the coloring was reduced over 15 minutes at 60°C in a water-based solution of 2 gpl sodium hydroxide (NaOH) as well as 2 gpl sodium hydrosulphite (Na 2 S 2 O 4 ). The investigation indicated that a 16% acetylation reagent dosage and a 2.5-hour reaction duration yielded a percent acetylation of 34 as the ideal measurement of acetylation [34]. Scheme 9: Process of cellulose's acetylation reactivity [34] The dyeing experiment's findings additionally indicated that, compared to the untreated halfbleached cloth, weft tensile strength was reduced by 9% and warp strain toughness by roughly 12% at a temperature of 120C.…”
Section: Dyeing Of Polyester/cotton Fabric Blendmentioning
confidence: 99%
“…Furthermore, in comparison with traditional two-bath colored fabric, one-step one-bath dyed altered PC blend with dispersion dye fabric exhibits superior durability properties, durability against abrasion, and tear toughness rating. The polyester/cotton one-bath, one-step coloring techniques using dispersion dye also demonstrated level dyeing's high color durability qualities and the technique's cost-efficiency [34]…”
Section: Dyeing Of Polyester/cotton Fabric Blendmentioning
confidence: 99%
See 2 more Smart Citations